2009
DOI: 10.1051/forest/2009028
|View full text |Cite
|
Sign up to set email alerts
|

Limitation de l’installation du chêne vert (Quercus ilex subsp. ballota (Desf.) Samp.) dans un écosystème de savane forestière méditerranéenne

Abstract: Abstract• Tree recruitment in Mediterranean savannas is generally hampered, in contrast with the original oak forests where these savannas are derived from. We asked whether this difference in recruitment success can be explained by differential post-dispersal survival. For one year we monitored experimentally cached holm oak acorns in a savanna -forest ecosystem in Central Spain, and recorded cache pilferage, type of pilferer, boar rooting, seedling emergence, seedling survival and the cause of mortality.• Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 33 publications
3
51
2
Order By: Relevance
“…Similarly, we did not find higher seedling emergence at closer distances to the islets where we expected higher emergence due to micro-climate amelioration by islet canopy shade. This contrasts with results in Smit et al (2009) showing higher emergence in shaded microsites than in open microsites and suggests a lack of ''safe'' microsites for recruitment in our experimental field (Pulido and Díaz 2005). It is possible that microclimatic amelioration by islet canopy was not enough to maintain high soil moisture during the dry spring, but we did not measure soil water content to assess this explanation.…”
Section: Lack Of Distance Effectscontrasting
confidence: 82%
See 1 more Smart Citation
“…Similarly, we did not find higher seedling emergence at closer distances to the islets where we expected higher emergence due to micro-climate amelioration by islet canopy shade. This contrasts with results in Smit et al (2009) showing higher emergence in shaded microsites than in open microsites and suggests a lack of ''safe'' microsites for recruitment in our experimental field (Pulido and Díaz 2005). It is possible that microclimatic amelioration by islet canopy was not enough to maintain high soil moisture during the dry spring, but we did not measure soil water content to assess this explanation.…”
Section: Lack Of Distance Effectscontrasting
confidence: 82%
“…For instance, Smit et al (2009) observed emergence values [90 % while Pulido and Díaz (2005) observed 73 % emergence in their study. Low emergence values in our study are probably a consequence of the dry spring, particularly in the few weeks after seeding.…”
Section: Low Seedling Emergencementioning
confidence: 76%
“…We selected 80 viable acorns following the same procedure as before and buried one acorn per microhabitat on all transects on October 23rd, 2007. Single acorns were buried horizontally at a depth of 2 cm to mimic a mouse-made cache (Den Ouden et al 2005;Smit et al 2009). To monitor the rates of seed removal in the different microhabitats, we checked the presence of the acorns at 3, 10, 85, 108, 135, and 198 days after burial.…”
Section: Post-dispersal Removal Experimentsmentioning
confidence: 99%
“…Those studies that measured high post-dispersal predation of acorns (Li and Zhang 2003;Iida 2006), therefore questioned the effectiveness of wood mice as dispersers. In contrast, many other studies underline the importance of seed dispersal by wood mice for tree regeneration despite high predation rates, as even a tiny fraction of acorns that escapes from post-dispersal seed predation may be sufficient for a substantial tree recruitment over time (Gómez 2004;Den Ouden et al 2005;Vander Wall et al 2005;Gómez et al 2008;Smit et al 2009). …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation